Psychological adaptation in women with endometriosis: current knowledge and future research perspectives. Issue 2 (7th February 2023) - Broc, G.; Porro, B.
ABSTRACT: This short report aims to present current knowledge on endometriosis. The daily repercussions of endometriosis and their impact on women's psychological state, the resentment often expressed towards doctors associated with diagnosis delay, influencing both appropriation and adaptation to the disease and driving women mainly to self-manage are discussed. Directions for research and intervention include the need to devise a comprehensive strategy in collaboration with stakeholders and to examine targeted study areas more thoroughly, notably related to work environment management, dietary changes and their consequences or the social representation of endometriosis among physicians, are proposed.